Ionic liquid post-modified carboxylate-rich MOFs for efficient catalytic CO2 cycloaddition under solvent-free conditions - Wen-Li, Bao; Kuai, Jie; Hai-Yang, Gao; Meng-Qi, Zheng; Zhong-Hua, Sun; Ming-Yang, He; Chen, Qun; Zhi-Hui, Zhang (Dalton transactions : an international journal of inorganic chemistry, 2024)
The synthesis of cyclic carbonates through cycloaddition reactions between epoxides and carbon dioxide (CO2) is an important industrial process. Metal–Organic Frameworks (MOFs) have functional and ordered pore structures, making them attractive catalysts for converting gas molecules into valuable products. One approach to enhance the catalytic activity of MOFs in CO2 cycloaddition reactions is to create open metal sites within MOFs. In this study, the amino-functionalized rare earth Gd-MOF (Gd-TPTC-NH2) and its ionic liquid composite catalysts (Gd-TPTC-NH-[BMIM]Br) were synthesized using 2′-amino-[1,1′:4′,1′′-terphenyl]-3,3′′,5,5′′-tetracarboxylic acid (H4TPTC-NH2) as the ligand. The catalytic performance of these two catalysts was observed in the cycloaddition reaction of CO2 and epoxides. Under the optimized reaction conditions, Gd-TPTC-NH-[BMIM]Br can effectively catalyze the cycloaddition reaction of a variety of epoxide substrates with good to excellent yields of cyclic carbonate products. Comparatively, epichlorohydrin and epibromohydrin, which possess halogen substituents, promote higher yields of cyclic carbonates due to the electron-withdrawing nature of Cl and Br substituents. Additionally, the Gd-TPTC-NH-[BMIM]Br catalyst demonstrated good recyclability and reproducibility, maintaining its catalytic activity without any changes in its structure or properties after five reuse cycles.